2002
DOI: 10.1136/bjsm.36.2.105
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety responses to 60 minutes of cross training: Figure 1

Abstract: Objectives: Significant reductions in state anxiety following bouts of aerobic exercise have been consistently noted, whereas changes are generally absent after acute resistance training. However, the influence of a single exercise session involving both modes on state anxiety has not been examined. Methods: To address this, state anxiety responses to 60 minutes of cross training were examined in 16 collegiate athletes (12 women, four men). Each subject completed two cross training exercise sessions (30 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…Higher scores indicate higher levels of anxiety. The SAI has been extensively validated and is the most widely used measure of anxiety in exercise research 2. The internal consistency assessed by Cronbach’s alpha coefficients in the present study was 0.96.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Higher scores indicate higher levels of anxiety. The SAI has been extensively validated and is the most widely used measure of anxiety in exercise research 2. The internal consistency assessed by Cronbach’s alpha coefficients in the present study was 0.96.…”
Section: Methodsmentioning
confidence: 57%
“…In 21 (87%) of the studies, acute exercise resulted in a significant reduction in state anxiety. It appears that acute aerobic exercise is more effective than weight training 1 2 3 4. In acute bouts of aerobic exercise, state anxiety reductions last for 2–4 h after cessation of activity 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results are relatively unequivocal in this respect. Immediately after a session of physical activity, most people report a decrease in state anxiety, which is still detectable 1-1.5 h after the end of the training (Cox et al, 2004;Hale et al, 2002;Knapen et al, 2009). While the short-term effects of acute physical activity on state anxiety are well documented, the long-term effects of chronic (habitual) physical activity on trait anxiety are still subject to debate: A meta-analysis by Herring et al 2010 confirmed the causal link between regular exercise and trait anxiety, whereas meta-analyses by Long and van Stavel (1995) and Schlicht (1994) did not find convincing evidence in support of this effect.…”
Section: Anxietymentioning
confidence: 99%
“…Es llamativa la modulación positiva sobre las funciones orgánicas generales, cómo son la inflamación (29,9), la inmunidad (8,30) o la distribución de los depósitos grasos (31). Y también se han apreciado mejorías de las funciones psíquicas, consistentes en un mayor optimismo (32), una menor ansiedad (33) y una mejora del sueño nocturno. Todos estos cambios propician, a cualquier edad, una mayor calidad de vida y disminuyen la morbi-mortalidad, no sólo cardiovascular, sino también global (34).…”
unclassified